Strategi Komisi Pemilihan Umum dalam Mengurangi Angka Golput pada Pemilihan Presiden dan Wakil Presiden - Nopi Amalia; Andi Mulyadi (JOPPAS: Journal of Public Policy and Administration Silampari, 2019)
This study aims to determine whether the strategy used by the KPU of Sukabumi City in the Presidential and Vice President Elections in Sukabumi City in 2019 can reduce the percentage of abstentions and achieve the targets set using the theory of G. Dess and Miller. This study uses a qualitative descriptive method, to determine the researcher's informant using snowball sampling. Data collection through observation, interviews, and documentation. In testing the validity of the data researchers used triangulation techniques. The results showed the percentage of abstentions in the election of President and Vice President in the City of Sukabumi had exceeded the target set by the KPU of Sukabumi City. One of the drivers of achieving this target is the Form A5 made by the KPU of Sukabumi City and the socialization targets provided by democratic volunteers. Conclusions, Sukabumi City Election Commission Strategy in reducing the number of abstentions in the election of President and Vice President has been going well Keywords: Strategy, Abstentions, General Election Commission